Impact of Dimethylformamide/Acetone Ratios and Stirring Time on Morphology and Electrical Properties of Electrospun PVDF Fibers - Hakimi Bin Ismail, M. I.; Syed Bakar, S. S.; Yahud, S.; Chaisitsak, S. (My University, 2025)
This study examines the impact of Dimethylformamide, DMF/Acetone ratio (60/40, 70/30 and 100/0) and stirring time (16 hours and 24 hours) on Polyvinylidene Fluoride electrospun fibers. Total of six samples were prepared at 12% solution con-centration were electrospun at 20 kV, 10 cm tip-to-collector distance, and 1 mL/h flow rate. Morphological analysis showed that a 70/30 ratio produced finer fibers with fewer beads than 60/40 ratio, while prolonged stirring increased fiber diameter. Electrical analysis confirmed the lowest resistance and highest conductivity for these fibers. The 70/30 ratio and 16-hour stirring time technique optimized fiber structure and electrical performance for advanced applications.
Keywords: Acetone; DMF; electrospinning; fiber; PVDF